The effect of ultrasound on the root meristem of Zea mays - Hering, Egbert Raymond (Department of Physics, 2026)
The first recorded effect of ultrasound - acoustical waves at a frequency above the audible range - on living organisms was produced by accident over 50 years ago. Chilowsky and Langevin (1916) had been investigating the ability of ultrasonic signals to detect underwater obstacles and had noted that if fish swam into the ultrasonic beam, they were instantly killed. The first deliberate attempt to affect biological material with ultrasound was also destructive; Wood and Loomis (1927) found that ultrasound could produce such diverse effects as the injury and death of small frogs and fish, the disruption of plant cells and protozoa, and the haemolysis of erythrocytes. In research that followed, it was noted that the sensitivities of various organisms are different and that some of the effect, such as partial paralysis, may be reversible. Some of the survival curves obtained in these early experiments were of the kind shown in Figure 1.1, which have the shape characteristic of all or nothing' effect of ultrasound (Grabar, 1953), i.e. a certain minimum sonication time and intensity is necessary to produce an effect. Perhaps the main value of this early work was that it stimulated research into the interaction between ultrasound and l living matter, research which led eventually to the therapeutic use of ultrasound. Gradually it was realised that destruction was only one of the proper11 ties of ultrasonic radiation, and that by careful regulation of the treatment parameters (frequency, intensity, treatment time and pulsing of the radiation) beneficial results could also be achieved (Dyson, Pond, Joseph and Warwick, 1968). Over the past ten years ultrasound has also become well established as the basis of a varied and expanding group of medical diagnostic techniques (Blitz, 1967; Brown and Gordon, 1967), and some misgivings over possible dangers, immediate or delayed, have arisen (Andrew, 1964; Connolly and Pond, 1967; Hill, 1968; Macintosh and Davey, 1970 and 1972). The clinical use of ultrasound has not been preceded by animal experimentation in which the model has been as sensitive as that in the clinical situation, as was the case when X-rays were first introduced as a diagnostic and therapeutic tool in medicine. For X-rays the possibility of any adverse effects was only realised when it was discovered that they were capable of sterilizing guinea pigs without any other obvious change in the well-being of the treated animals (Albers-Schoenberg,1903). However, recent results of animal experimentation, using diagnostic ultrasonic devices, have failed to disclose any deleterious effects (Woodward, Pond and Warwick, 1970; Taylor and Dyson, 1972). The nature and extent of the biological effects are, however, still uncertain (Hill, 1968). It therefore seems important to have a clear understanding of the factors that determine whether any potentially harmful forms of biological change may arise in 12 the course of any of the applications to which ultrasound is being put at present. In parallel with this development a revival has occurred in studies of the mode of biological action of this form of radiation and, at the same time, "it has become apparent that the significance of much of the extensive pioneering work in this field is vitiated by the lack of an adequate system for measuring and reporting physical parameters of irradiation" (Hill, 1970). Since the present studies are on the effects of ultrasound on the root meristem of the maize plant, the next few paragraphs will be devoted to this particular aspect of ultrasound biology.